Aqueous Ozone Sanitization System for Fresh Produce: Design, Development, and Optimization of Process Parameters for Minimally Processed Onion. (2nd January 2022) - Aslam, Raouf; Alam, Mohammed Shafiq; Pandiselvam, R.
ABSTRACT: The study was carried out to design and develop an ozonation treatment system for the sanitization of fresh produce before storage. The developed system was evaluated for minimally processed onions based on the kinetics of degradation, application methods, homogeneity of dissolution, and specific energy consumption. The sanitization process was then optimized for cut onion slices using a Box-Behnken design under Response Surface Methodology to study the effects of ozone concentration (1–5 ppm), exposure time (3–8 min), and aqueous pH (3–5) on microbial log reductions, pyruvate content, color change, and overall acceptability. The results obtained showed that degradation kinetics of dissolved ozone followed a first-order reaction with a half-life of 18.23 min. Among the different methods of ozone application tested at 5 ppm ozone concentration, the splashing method yielded the highest microbial log reductions (5.04) followed by dipping (4.5) and spraying (4.22) methods. For the sanitization of cut slices of onion, it was observed that aqueous ozone at 5 ppm concentration splashed on the surfaces for 8 min and an aqueous pH of 3.01 yielded optimized sanitization, whereas microbial log reductions, pyruvate content, and overall acceptability were recorded as 5.6 log reductions, 0.127 µM/mL, and 8.2, respectively. Overall, the system was found to be effective for the sanitization of minimally processed onions.